Use of erythropoiesis-stimulating agents in patients with anaemia of chronic kidney disease. Issue 2 (12th March 2012) - Larrodé, I.; Navarro, H.; Alonso, Y.; Gómez, C.; Cañamares, I.; Abad, R.
Abstract : Background: Anaemia is a common complication of chronic kidney disease (CKD), and its correction with erythropoiesis-stimulating agents (ESAs) is associated with improved patient outcomes and quality of life. Purpose: To evaluate the demographic and clinical characteristics of outpatients with CKD and anaemia, treated with epoetin alfa (EPO) or darbepoetin alfa (DARB). To compare the use of ESAs in predialysis patients. Materials and methods: Descriptive observational study, including patients with CKD and treated with ESAs, recorded in our pharmacy outpatient database and treated with ESAs, from March to July 2011. Data collected: age, gender, GRF, cause of CKD, ESA prescribed, dosage of ESA; during the period the latest data of haemoglobin (Hb), serum ferritin level and transferrin saturation were recorded. Use of ESAs was assessed in the group of predialysis patients (stage 3 and 4 of CKD) with Hb levels between 10 and 12 g/dl (the current FDA and EMA targets). Results: 476 patients were recorded (51.5% men, average age 69.4±15.6 years). 376 patients received EPO and 100 DARB. Hb levels: 10 to 12 g/dl (45.2%), < 10 g/dl (10.9%) and > 12 g/dl (43.9%). 18.4% of patients had Hb level >13 g/dl. CKD stages: stage 3 (30.6%), 4 (45.7%) and 5 (home dialysed patients) (19.2%). Subgroup of predialysis patients with Hb level between 10-12 g/dl: 155 patients (average age 70±16.4 years, 51% men), 77% with EPO and 23% DARB. Significant differences in EPO versus DARB patients were found in: average age (71.2 vs 65.0, p=0.04), men (55.5% vs 36.0%, p=0.04), the use of extended dosing (≥q 2 wk) (24.4% vs 66.7%, p<0.001). Mean weekly doses in each: 4986 IU (EPO) versus 25.88 mcg (DARB). Conclusions: A high number of patients were above the safe limit (12 g/dl); action must be taken to improve the quality of pharmacotherapy. The dose ratio within EPO and DARB was 192:1.